2019
DOI: 10.1039/c8bm01224e
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol-loaded PEG-b-PPS nanocarriers as an anti-inflammatory treatment for atherosclerosis

Abstract: Encapsulation within poly(ethylene glycol)-b-poly(propylene sulfide) micelles reduces the toxicity of celastrol and enhances its anti-inflammatory effect during treatment of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 71 publications
1
57
0
1
Order By: Relevance
“…After 2 hours of exposure to various doses of (+)MiNP and Free LatA, (+)MiNP treated macrophages remained highly viable at all tested concentrations, while free LatA treated macrophages demonstrated significant toxicity at doses of 0.5 μM and above (Figure 2e). This is consistent with our previous findings in which encapsulation of small molecule drug Celastrol reduced its cytotoxicity in vitro [20] .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…After 2 hours of exposure to various doses of (+)MiNP and Free LatA, (+)MiNP treated macrophages remained highly viable at all tested concentrations, while free LatA treated macrophages demonstrated significant toxicity at doses of 0.5 μM and above (Figure 2e). This is consistent with our previous findings in which encapsulation of small molecule drug Celastrol reduced its cytotoxicity in vitro [20] .…”
Section: Resultssupporting
confidence: 94%
“…These micelles have also been previously shown to reduce the cytotoxicity of small molecule drugs such as celastrol. [20] Here, we employ macropinocytosis inhibitory nanoparticles (MiNP) to reduce non-specific nanoparticle uptake by the MPS and enhance their accumulation within target tissues. MiNP are comprised of PEG-b-PPS micelles containing Latrunculin A (LatA), a well-known and transient actin depolymerizing agent [21] .…”
Section: Introductionmentioning
confidence: 99%
“…As a natural product, celastrol was mainly extracted from Tripterygium wilfordii and listed as one of the five traditional natural medicinal compounds most likely to be developed as modern drugs (Corson & Crews, 2007). Celastrol revealed multiple activity on immunity (Dudics et al, 2018), diabetes (Pfuhlmann et al, 2019) and inflammatory (Allen et al, 2019) and tumor diseases (Li et al, 2019). To reduce its toxicity and optimize its pharmacological properties, many superior derivatives were generated as indicated in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Targeted nanomaterials have been shown to lower the therapeutic threshold concentration for cer tain drugs after encapsulation as well as reduce cytotoxicity and other unwanted effects in many cell types including SC cells. [11][12][13] Latrunculin is a wellknown transient actin depolymerizing agent that mechanically softens cells [14] and has been shown to significantly reduce IOP in animal studies. [5,15] A phase I clinical trial, at concentrations previously found to be effective in primates, found a modest reduction of IOP with side effects that included mild redness, irritation, and a transient increase in central corneal thickness.…”
Section: Doi: 101002/smll202004205mentioning
confidence: 99%